Fatores de usabilidade em ambiente de educação a distância: estudo exploratório do ambiente virtual de aprendizagem do curso de Mediação de Conflitos Socioambientais da Fundação do Desenvolvimento Administrativo do Governo do Estado de São Paulo - Sebastião, Márcia Pereira (2009)
The e-learning has had an important role in contemporary education scenario in national and global. As experience grows with the systematic use of Virtual Learning Environments, problems arising from such use have been reported. Often, related to such factors as: a) the enormous amount of information that needs to be managed and at the same time, be available for teachers and students, b) the interactions between the various participants in the process, c) the difficulty of understand that the activities of others have a direct impact on their own activities. Therefore, there is a need for care related to the quality of interactions available in the Web Thus, developing an interface with an ease of navigation and interaction is crucial for the smooth running of courses developed in the e-learning. To this scenario, this research aims to investigate the usability of the application sites in e-learning, aiming to improve user interaction with the interface. Thus, the method used for data collection consists of: application of heuristic analysis, thematic content analysis of semi-open questionnaires applied of intertext harvested in the Community Course in screen: Curso de Mediação de Conflitos Socioambientais. The analysis of data collected was interpreted in the light of the following theoretical framework: the e-learning (historical, philosophical concepts, approaches educacioanis), cyberspace, usability and accessibility of digital devices and interfaces (heuristic analysis of Nielsen, CC-9 Resolution of the Government of State of São Paulo, 2005). The study demonstrates the usability of devices and digital interfaces as a key to the successful development of online courses. The analysis of interfaces in e-learning courses is of great importance, since the problem of non conductive interfaces, difficult learning and memory, and with high incidence of errors, tends to negatively impact the user. More than the ix technological sophistication, it is the serious study of the usability of the environment in question